Evaluation of vestibular and oculomotor functions in individuals with dizziness after stroke - Bianca Nunes Pimentel; Valdete Alves Valentins dos Santos Filha (Arquivos de Neuro-Psiquiatria)
ABSTRACT Changes in postural balance and visual complaints are frequent consequences of stroke. We aimed to investigate the symptoms and the vestibular and oculomotor functions of patients with dizziness post ischemic and hemorrhagic stroke and compare the results among them. Methods: Fifty patients with dizziness after stroke were evaluated through a clinical anamnesis and computerized vector electronystagmography: calibration of ocular movements, spontaneous nystagmus, semi-spontaneous nystagmus, pendular tracking, optokinetic nystagmus, rotary chair testing, and the caloric test. Results: All patients complained of dizziness, especially imbalance. Ischemic stroke in the carotid territory was the prevalent type. Visual complaints were reported by 56% of the sample and were related to abnormalities in oculomotor and caloric tests. Conclusion: The occurrence of visual symptoms was related to some abnormalities in the vector electronystagmography tests, being more frequent in cases of stroke in the vertebrobasilar system, and with oscillopsia and reduced visual acuity as symptoms.